Моделювання продуктивного тиску в неоднорідних нафтоносних пластах - Лубков, М.В. (Геоінформатика, 2017)
З метою дослідження продуктивного тиску в неоднорідних нафтоносних пластах на основі комбінованого скінченно-елементно-різницевого методу для нестаціонарної задачі п’єзопровідності виконано чисельне моделювання розподілу падіння пластового тиску в околі діючих свердловин з урахуванням неоднорідного розподілу характеристик проникності в колекторських пластах і на межах родовища. Показано, що процеси падіння пластового тиску в околі діючих свердловин суттєво залежать від пористості, проникності колекторських порід і в’язкості газорідкої фази пласта, а також від характеру проникності порід на межах родовища. Зменшення пористості та проникності пласта, збільшення в’язкості його газорідкої фази призводять до помітного зменшення видобування нафти. Розміщення нагнітальних свердловин на відстані не більш як 1,5 км від діючих свердловин зумовлює збільшення пластового тиску і, відповідно, зростання видобутку. Показано, що регулювання робочих тисків у добувних і нагнітальних свердловинах дає змогу досягти оптимальних умов видобутку нафти. С целью исследования продуктивного давления в неоднородных нефтеносных пластах на основе комбинированного конечноэлементно-разностного метода для нестационарной задачи пьезопроводности выполнено численное моделирование распределения падения пластового давления в окрестностях действующих скважин с учетом неоднородного распределения характеристик проницаемости в коллекторских пластах и на границах месторождения. Показано, что процессы падения пластового давления в окрестностях действующих скважин существенно зависят от пористости, проницаемости коллекторских пород и вязкости газово-жидкой фазы пласта, а также от характера проницаемости пород на границах месторождения. Уменьшение пористости и проницаемости пласта, увеличение вязкости его газово-жидкой фазы приводят к заметному уменьшению добычи нефти. Размещение нагнетательных скважин на расстоянии не более 1,5 км от действующих скважин обусловливает увеличение пластового давления и, соответственно, рост добычи. Показано, что регулирование рабочих давлений в добывающих и нагнетательных скважинах позволяет достичь оптимальных условий добычи нефти. Purpose. The problems connected with increasing of efficiency of development and operation of oil-bearing deposits are growing ever more important today. They are caused by the rapid growth of oil production, associated with reducing its water overflowing, increasing oil recovery, to achieve economic efficiency. In this situation, there are popular methods of computer modeling of productive reservoirs, which allow one to get information on the structure and characteristics of the reservoir, as well as the distribution parameters of permeability and fluids in it. They also permit to evaluate and calculate uncertainty arising from the lack of information about the reservoir properties outside the well. Currently there exist many methods of computer modeling, which solve various practical problems. On the other hand, there are a number of problems related to the accuracy and adequacy of simulation of heterogeneous multiphase permeable collector systems in real-term exploitation of oil deposits. Design/methodology/approach. On the basis of the combined finite-element-difference method for solving the nonstationary piezoconductivity problem, calculating heterogeneous distribution of permeable characteristics of the collector deformable reservoir, we carried out modeling of the producing pressures in oil-bearing reservoirs. Findings. The results of computer modeling show that the drop of reservoir pressure in the vicinity of acting wells depends primarily on collector properties of the reservoir and permeable character on the boundaries of the deposit. The nature of the drop of reservoir pressure near acting wells is similar in character to the radial. During exploitation, radius and slope of the area of falling reservoir pressure around the well are gradually increasing. Moreover, the speed of this process is determined by collector reservoir characteristics (porosity, permeability, viscosity of gas-liquid phase), and by the character of permeability of collector rocks on the boundaries of the deposit. Reducing the porosity and permeability of the reservoir and increasing the viscosity of gas-liquid phase lead to a noticeable drop in oil production. Location of injection wells at distances not exceeding 1.5 km from the production wells results in a significant increase of the reservoir pressure in the vicinity of these wells and, accordingly, to the increase of oil production. Practical value/implications. The obtained results may be used in practical geophysical works with the purpose of optimizing oil production activity. The presented method may further be used for more detailed investigation of heterogeneous oil-bearing deposits.